Insomnia as a Moderator of Response to Time in Bed Restriction for Augmenting Antidepressant Treatment: A Preliminary Investigation. Issue 4 (4th July 2018) - Swanson, Leslie M.; Huntley, Edward D.; Bertram, Holli; Mooney, Ann; Dopp, Richard; Hoffmann, Robert; Armitage, Roseanne; Arnedt, J. Todd
ABSTRACT: Background: There are complex, bidirectional associations between major depressive disorder and insomnia. In the present study, we evaluated insomnia as a moderator of response to antidepressant therapy in the context of a sleep manipulation (time in bed restriction) for major depressive disorder. Methods: Fifty-eight adults with major depressive disorder received 8 weeks of fluoxetine 20–40 mgs and were randomized to 8 hr time in bed (8h TIB) or 6 hr time in bed (6h TIB) for the first 2 weeks (participants in the 6h TIB condition were further randomized to a delayed bedtime (Late Bedtime) or advanced rise time (Early Rise Time) group). Insomnia was assessed at baseline using the Insomnia Severity Index. Depression symptom severity was determined by the clinician-rated 17-item Hamilton Rating Scale for Depression (HAMD-17), completed weekly. Results: A group by time interaction was observed whereby HAMD-17 scores were higher for participants assigned to the 6h TIB group (without insomnia, weeks 3 through 7; with insomnia from week 3 through 6, p s < .05) relative to participants without insomnia assigned to the 8h TIB group. There were no differences in HAMD-17 scores for participants with insomnia in the 6h TIB group relative to the 8h TIB group. Conclusion: These preliminary findings suggest that response to fluoxetine may be hindered by TIB restriction in individuals without insomnia. Individuals with insomnia respond similarly to fluoxetine regardless of whether their TIB is restricted. Limitations include exclusive use of self-report measures to categorize insomnia, and small sample sizes in several of the subgroups.